Edible insects, a sustainable option? Perceptions of a sample of Portuguese citizens - Guiné, Raquel P. F. (2022)
PURPOSE Edible Insects (EI) have been pointed by many as a sustainable option to provide animal protein, thus contributing to a more sustainable food system. However, not all societies are prone to consume this type of food (Florença et al., 2021). So, this study intended to evaluate to what extent the Portuguese are informed about the sustainability issues related with EI. METHODS This study was based on a questionnaire developed by the team of the project FZ (Ref. PROJ/IPV/ID&I/013) and was approved by the Ethics Committee at the Polytechnic Institute of Viseu (Ref. N.º 06/SUB/2020). The online tool Google Forms was used to collect the data anonymously. At the beginning of the form the respondents were presented with the declaration of informed consent, and only those who gave explicit consent and were legally adult citizens, were able to access the questionnaire to give their answers. The data collection took place between September and October 2020, and the number of responses obtained was 213. The data were explored by descriptive statistic tools, tree classification analysis, factor analysis and cluster analysis. RESULTS AND DISCUSSION The results revealed that the Portuguese people’s level of information about the sustainability issues related with EI is still low in general, with an expressive percentage of “no answer”. Still, there are some particular aspects that are already familiar to the participants (89% know that EI have a lower ecological footprint than other meats and 87% know that EI efficiently convert feed into protein). Factor and cluster analysis showed three classes of participants: first cluster - participants not informed about the facts presented, regardless of being true or false); second cluster - participants not informed about the true statements but who were able to identify the false statements; and third cluster - participants well informed about the true statements but who were marginally unable to distinguish the false information. Additionally, it was observed that sociodemographic variables such as education, sex and professional area were the most important influencing factors on the level of information. IMPLICATIONS Although there is already among the Portuguese some awareness that EI can be a more sustainable alternative to other types of meat, there is still a need to better inform the general population about the consequences of more sustainable food choices, to motivate them into innovative trends. Producers and brands should provide information to educate and inform possible future consumers about EI, their advantages and other issues related to this type of food to promote it on not typical markets. Nevertheless, industrials and other actors in the food chain must be conscious that part of the consumers will continue to feel aversion or disgust towards EI, as a result of personal traits and cultural imprints.